Roman Catolic Church and Confessional Revival. (In)tolerance in a Complex Borderland up to 1630s. Case Study of the Town of Koprivnica - Petrić, Hrvoje (2007)
Multi-ethnic confessions of Koprivnica were particularly obvious in late 16th century and the first decades of 17th century. In the beginning of 17th century, Koprivnica was settled with Serb Orthodox Vlach population, coming over with the military. By the end of 17th century, it was the Orthodox, or so-called &laquo ; Greek&raquo ; trading population. Around 1630, Roman Catholic Church in Koprivnica was at the same time busy with reorganization of finances and military establishment in Slavonnian Border (Varaždin Generalate). It's interesting to notice, that soon after 1630, Koprivnica got rid of the Protestants ; the original Serb Orthodox Vlach population was no longer traceable in history sources, which indicates religious intolerance. This intolerance is clearly visible in the example of a small group of Moslem settlers, who were systematically baptized and converted to Christianity. Although we only know a few records on confessional converting of Koprivnica townspeople in various directions, this daring, yet delicate subject, remains open to further research.
Projekt MZOS
ENG